Relationship Between Physical Fitness, Physical Activity, and Different Anthropometric Parameters in School Children in Santiago (Chile) [Relación Entre Condición Física, Actividad Física y Diferentes Parámetros Antropométricos en Escolares de Santiago (Chile)] - Cofre-Bolados, C (ARAN Ediciones S.A., 2016)
Introduction: Society is currently experiencing significant reductions in physical activity levels and increases in sedentary behavior are associated with obesity. Objective: The aim of this study was to identify the prevalence of overweight and obesity in a group of school children in Santiago, Chile and explore the relationship between body composition, physical activity and physical fitness. Material and methods: Research was conducted with a representative sample of 515 students (10.6 ± 0.5 age-old). Data included their anthropometric measurements (BMI and fat percentage), physical activity, and physical fitness (aerobic capacity, lower-body and upper-body explosive strength). Results: About 55% of the sample was overweigh/obesity. Male students and students with normal body weight fared better in physical fitness tests than females and those who suffered from overweight or obesity. We found inverse relationships between the PAQ-C score and anthropometric parameters and between anthropometric parameters and physical fitness. Conclusion: Given the alarming levels of childhood overweight and obesity detected in Santiago and the relationship between physical fitness and body composition it is important to design interventions which can induce improvements in physical fitness, and specifically target females and children with obesity. © 2016, ARAN Ediciones S.A. All rights reserved.